Galaxy as dynamical system with accreting cold gas halo - Berczik, P.; Kravchuk, S.G. (Кинематика и физика небесных тел, 1997)
Recent observational data argue that beside the nonbaryonic component, the halo of our Galaxy contains a significant fraction of baryonic matter. The time evolution of the galactic disk surface density depends strongly on baryonic halo properties. In order to estimate its parameters, we have carried out numerical simulations of the evolution of the galactic system having additional baryonic halo in the form of “invisible” small hydrogen clouds. It was found that only model with baryonic halo having initial mass of 2∙10¹¹ M⊙ and flat rotation curve fits well the galactic disk properties in the solar cylinder. Нові спостережні дані вказують на те, що крім небаріонного компонента в гало нашої Галактики присутня помітна доля баріонної матерії. Еволюційна поведінка поверхневої густини галактичного диску сильно залежить від параметрів баріонного гало. Для того щоб оцінити його параметри, ми провели числове моделювання еволюції галактичної системи з додатковим баріонним гало у формі «невидимих» маленьких водневих хмарок. Виявилось, що модель з баріонним гало, яке має початкову масу 2∙10¹¹ M⊙ і плоску криву обертання, адекватно описує властивості галактичного диска в сонячному циліндрі. Новые наблюдательные данные указывают на то, что кроме небарионного компонента гало нашей Галактики содержит заметную долю барионного вещества. Эволюционное поведение поверхностной плотности галактического диска сильно зависит от параметров барионного гало. С тем чтобы оценить его параметры, мы провели численное моделирование эволюции галактической системы, обладающей дополнительным барионным гало в форме «невидимых» маленьких водородных облачков. Оказалось, что модель с барионным гало, имеющим начальную массу 2∙10¹¹ M⊙ и плоскую кривую вращения, адекватно описывает свойства галактического диска в солнечном цилиндре.